DAMPAK INTENSITAS PENGGUNAAN TIKTOK TERHADAP PELAKSANAAN SHALAT WAJIB PADA MAHASISWA - Afifah, Nazwa Nur; Amelia, Ica; Al Ghifari, Noor Muhammad; Faqihuddin, Achmad (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2025)
The development of information technology and social media, especially TikTok, has had a significant impact on daily life, including the implementation of spiritual obligations such as prayer among students. This study aims to analyze the effect of the intensity of TikTok use on the implementation of obligatory prayers. This research method uses a qualitative approach with an online survey involving 43 students as respondents. The results showed that 86.04% of respondents admitted that they often postponed prayers because they were distracted by TikTok content, especially during the Isha prayer time. Dependence on this application can reduce the priority of worship obligations. Although the majority of respondents are aware of the importance of self-discipline and spiritual awareness, interest in digital content often affects time management. This study emphasizes the need to increase self-awareness, discipline, and time management for students to prevent neglect of worship. The main recommendation is to utilize the prayer reminder feature and limit the duration of TikTok use, so that the balance between digital entertainment and spiritual obligations can be maintained.